2018
DOI: 10.1016/j.watres.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, nutrient-balancing and biological treatment of hand washing greywater

Abstract: On-site biological hand washing water treatment can improve global access to safe hand washing water, but requires a thorough understanding of the chemical composition of the water to be treated, and an effective treatment strategy. This study first presents a detailed characterization of the individual inputs to hand washing water. We demonstrate (i) that soap is likely the most significant input in hand washing water, representing ∼90% of mass loading, and (ii) that inputs to hand washing water have low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Long-term testing with a BAMBi fed a mixture of feces, urine, soap and water has demonstrated 95% removal of organic carbon (Künzle et al., 2015) as well as stable nitrification and denitrification (Ravndal et al., 2015). Similar performance has been demonstrated treating a synthetic hand washing greywater (Ziemba et al., 2018). BAMBi utilizes a gravity-driven membrane (GDM) which requires no additional pressure to be applied to the feed side of the membrane beyond the weight of water.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Long-term testing with a BAMBi fed a mixture of feces, urine, soap and water has demonstrated 95% removal of organic carbon (Künzle et al., 2015) as well as stable nitrification and denitrification (Ravndal et al., 2015). Similar performance has been demonstrated treating a synthetic hand washing greywater (Ziemba et al., 2018). BAMBi utilizes a gravity-driven membrane (GDM) which requires no additional pressure to be applied to the feed side of the membrane beyond the weight of water.…”
Section: Introductionsupporting
confidence: 65%
“…The recipe for the synthetic feed was taken directly from, and is described in great detail by, Ziemba et al. (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study had also reported that handwashing soap is the dominant ingredient in the handwash water [36]. In the handwash area the students were instructed not to use any soaps as that could potentially increase the nutrient level in the HW water.…”
Section: System Descriptionmentioning
confidence: 99%
“…Photocatalytic ozonation reduced approximately 60% of total organic carbon (TOC) and 97% of bacterial content from graywater, while the combination with electro-MBR increased TOC removal to 80%. Ziemba et al (2018) studied the use of a household-scale biologically activated MBR (BAMBi) system to treat graywater for potential reuse. Supplemental nutrients were used to increase the reduction of organic carbon to 95%.…”
Section: Mf-ro-aopmentioning
confidence: 99%